EKSPLORASI TEKNIK PEWARNAAN ALAM DENGAN EKSTRAK KAYU JAMBAL PADA BATIK KAYU GEMPOL - Waridah Muthiah; Lia Evvyani (Universitas Mercu Buana, 2019)
Gempol is a type of wood that is widely used as a craft material. Because the nature of the material is not too hard, easy to form, easy to absorb the liquid dye, and not greasy, this wood is suitable to be processed with various techniques, including wooden batik. Because of its uniqueness, wooden batik has good potential to be developed in the craft industry. However, the technique used in the process of making wooden batik tends to be harmful to the environment, because it uses synthetic dyes. Natural dyes are rarely developed for wood batik because they are considered not good in terms of color quality and time efficiency. This study seeks to explore the use of natural dyes extract of jambal wood on gempol wood, through various types of mordants, coloring and mordanting methods, and coloring times. The research was carried out using an experimental method with the AHP method to obtain the ideal coloring method and material formulation.